Pemeriksaan Kualitatif Hidrokuinon dan Merkuri dalam Krim Pemutih - Roslinda Rasyid; Eva Susanti; Rieke Azhar (STIFARM Padang, 2015)
Studies have been conducted to analyse the hydroquinone and mercury content in beauty whitening creams from parlor and on the market in Padang city. Beauty whitening cream samples were A, B, C, D,E and F, then were observed using FeCl3, Ag-ammoniacal, Sodium Hydroxide, Potassium Iodide, and amalgam reagents. Hydroquinon was determined using Thin Layer Cromatography (TLC) and UV spectrophotometer. The results showed that six samples from three samples whitening cream B, D and F identified containing hydroquinone and two samples B and F contain mercury. So from the six samples of beauty whitening cream, three samples of the products do not contain hydroquinone and mercury.